2015
DOI: 10.1016/j.indcrop.2015.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Variations in key artemisinic and other metabolites throughout plant development in Artemisia annua L. for potential therapeutic use

Abstract: Dried leaves of Artemisia annua show promise as an inexpensive and sustainable antimalarial therapeutic, especially for use in developing countries. Along with the potent terpene, artemisinin, many other small molecules produced by the plant seem to aid in the therapeutic response. However, little is known about the ontogenic and phenological production of artemisinin in the plant, and its plethora of other important secondary metabolites. From a consistently high artemisinin-producing A. annua clone (SAM) we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 46 publications
4
27
0
1
Order By: Relevance
“…Two Artemisia annua L. clonal cultivars propagated by rooted cuttings (Towler and Weathers, 2015; Weathers and Towler, 2012) were used in this study: SAM (DLAS) (voucher MASS 00317314), a high AN-producing cultivar (~1.4% w/w), and GLS (DLAG) (vouchers OR State Univ 171772 and 170353), a glandless AN-null mutant cultivar with no glandular trichomes that produces no AN (Duke et al, 1994) and 25% of the flavonoids found in SAM. SAM plant material used in protein and dietary constituent experiments was field grown in Stow, MA, harvested at floral budding stage, dried and processed as previously described (Weathers et al, 2014b).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Two Artemisia annua L. clonal cultivars propagated by rooted cuttings (Towler and Weathers, 2015; Weathers and Towler, 2012) were used in this study: SAM (DLAS) (voucher MASS 00317314), a high AN-producing cultivar (~1.4% w/w), and GLS (DLAG) (vouchers OR State Univ 171772 and 170353), a glandless AN-null mutant cultivar with no glandular trichomes that produces no AN (Duke et al, 1994) and 25% of the flavonoids found in SAM. SAM plant material used in protein and dietary constituent experiments was field grown in Stow, MA, harvested at floral budding stage, dried and processed as previously described (Weathers et al, 2014b).…”
Section: Methodsmentioning
confidence: 99%
“…AN in extracts was quantified using GCMS according to the method detailed in Towler and Weathers (2015). Flavonoids in extracts were quantified using the spectrophotometric AlCl 3 method (Arvouet-Grand et al, 1994) with quercetin as a standard.…”
Section: Methodsmentioning
confidence: 99%
“…Artemisinic and flavonoid analyses are detailed elsewhere (Towler and Weathers 2015). Briefly, the five artemisinic compounds were analyzed from methylene chloride extracts of weighed fresh tissues using GCMS via their retention time, ion signatures, comparison to authentic external standards, and some published mass spectra .…”
Section: Artemisinic Metabolite and Flavonoid Analysismentioning
confidence: 99%
“…For example, variations in metabolites throughout plant development in Artemisia annua was reported [16]. Chemical changes and antioxidant activity in pomegranate arils during fruit development was also noticed [17].…”
Section: Total Phenols and Flavonoidsmentioning
confidence: 99%